Agricultura familiar com base tecnológica orgânica: potencial de expansão no Território Sudoeste do Paraná - Picinatto, Antonio Carlos (2010)
From a study about APOP Organic Producers Association of Pérola do Oeste, Paraná state, we identify difficulties that family agriculture based on organic technology faces to expand it self in the Territory Southwest of Paraná. We rescue information for understanding the territorial dynamics emphasizing, since 1950, when APOP´s family members came to county and bought their farms. The study examines the views of family farming organizations (Cresol System, System Coopafi, Sisclaf, Cooperiguaçu, Assesoar), private initiatives (Gebana, Gralha Azul) and government (Emater). We identified local experiences of organic agriculture for municipalities to demonstrate the territorialization that occurs in the Southwest of Paraná. The potential expansion of organic agriculture is defended by all respondents, in spite of differences of how to do it. The concordances are about activities that have greater potential to expand, were mentioned in horticulture and organic milk. The arguments for these activities emphasize that the organic model does not generate more work than the conventional model. The directors of the studied organizations suggest that family farms invest in food production for the population of the Territory.